Sirtuin-3: A potential target for treating several types of brain injury - Yang, Hongqiao; Zhou, Zhaopeng; Liu, Zhuanghua; Chen, Junhui; Wang, Yuhai (Frontiers in Cell and Developmental Biology, 2023)
Sirtuin3, a small molecule with a molecular weight of 28 kDa, exists in mammalian cell mitochondria and plays a powerful biological function. Sirtuin3 (Sirt3) is responsible for maintaining mitochondrial homeostasis by deacetylating substrates, which depend on NAD+. Sirt3, the primary deacetylase in mitochondria, controls cellular energy metabolism and the synthesis of essential biomolecules for cell survival. Sirt3 has been widely studied in many diseases of multiple systems. Sirt3 is closely related to neurodegenerative diseases in the central nervous system. In recent years, sirt3 has been increasingly reported in several kinds of acute brain injury and has become an essential focus of researchers' attention. In ischemic stroke, subarachnoid hemorrhage, traumatic brain injury, and intracerebral hemorrhage, the role of sirt3 is closely related to mitochondrial homeostasis, and it is also closely associated with the mechanism of pathophysiological processes such as neuroinflammation, oxidative stress, autophagy, and programmed cell death. As sirt3 is the driver and regulator of a variety of pathophysiological processes, the molecular regulation of Sirt3 is significant. Here, according to the biological function of sirt3, we review the role of sirt3 in several kinds of brain injury (I/R, SAH, TBI, ICH) and summarize the molecular regulation of sirt3. Numerous studies have demonstrated that sirt3 plays a protective role in various types of brain injury. We introduce the latest research on sirt3 as a target for treating ischemic stroke, subarachnoid hemorrhage, traumatic brain injury, and intracerebral hemorrhage, thus emphasizing sirt3's therapeutic potential as a powerful mediator of catastrophic brain injury. In addition, we summarized the therapeutic drugs, compounds, natural extracts, peptides, physical stimuli, and other small molecules that may regulate sirt3 to uncover more brain-protective mechanisms of sirt3, conduct more research, and provide more evidence for clinical transformation and drug development.